ANALISIS KELAYAKAN FINANSIAL DAN RISIKO USAHA BUDIDAYA JAMUR TIRAM DI PROVINSI LAMPUNG - Devy, Jenisa; Hasyim, Ali Ibrahim; Situmorang, Suriaty (Jurnal Ilmu Ilmu Agribisnis: Journal of Agribusiness Science, 2018)
This research aims to analyze the financial feasibility and the risk of oyster mushroom cultivation which is conducted in Lampung Province, especially in Metro and Bandar Lampung City.  The locations of the research are chosen purposively by considerating that both places were the largest harvesting areas and the highest oyster mushroom production.  The data is collected in month of May 2017, in which respondents are taken by census method with the amount of seven cultivators. They are divided into three categories based on their techniques they use, i.e., the cultivators producing the  planting media to be cultivated and partly to be sold, the cultivators producing the planting media to be cultivated only, and the cultivators purchasing the planting media to be cultivated.  Furthermore, the financial and risk analyses are analyzed by the quantitative analysis.  The result showed that the oyster mushroom cultivation on the three categories were profitable and feasible to be developed based on the value of investment criterias (Internal Rate of Return (IRR), Net Present Value (NPV), Payback Period (PP), Gross Benefit Cost Ratio (Gross B/C Ratio) and Net Benefit Cost Ratio (Net B/C Ratio)).  The risk analysis showed that CV (Coefficient of Variation) value was ≤ 0,5 and value of lower limit (L)was  ≥ 0; hence the cultivators were able to avoid the risk.Key words : cultivator, feasibility, financial, oyster mushroom, risk